Advancements and Challenges in Electric Vehicle Battery Charging: A Comprehensive Review - Dhanadhya Trupti; Kadam Swaraj; Prasad Shashikant; Vaidya Harshal (E3S Web of Conferences)
Electric vehicles (EVs) stand out as more efficient in conserving energy, reducing emissions, and safeguarding the environment compared to their fuel-powered counterparts. Consequently, as they find broader applications in the transportation industry, their significance continues to grow. The impending reality of widespread EV adoption is evident as their usage increases daily. In the shift towards the electronic revolution within the automotive sector, the manner in which EVs are charged becomes a pivotal concern. This comprehensive review examines recent advancements and persistent challenges in EV battery charging technologies. The paper analyzes various charging methodologies, including conductive, inductive, and battery swapping systems, evaluating their technical characteristics, implementation challenges, and impact on charging infrastructure. Key developments in fast-charging protocols, wireless power transfer efficiency, and smart grid integration are discussed. Critical challenges addressed include charging time optimization, infrastructure scalability, standardization issues, and grid stability concerns. The review also explores emerging technologies such as dynamic wireless charging and along with their potential impact on future EV adoption. Finally, the paper identifies research gaps and suggests future directions for improving EV charging technologies. This systematic review provides valuable insights for researchers, industry practitioners, and policymakers working towards advancing sustainable transportation solutions.